Comorbidity between PTSD and Anxiety and Depression: Implications for IAPT Services - Rachel Thomlinson; Steven Muncer; Helen Dent (Archives of Depression and Anxiety - Peertechz Publications, 2017)
Objective:  The Improving Access to Psychological Therapies (IAPT) initiative was introduced in the UK to increase access to psychological therapies for those with mild to moderate anxiety and depression. Recent outcome figures suggest recovery  rates  of  42%. One  potential reason for non-recovery is the experience of previous trauma and potential  PTSD comorbidity,  which has been found to negatively impact treatment for anxiety and depression. This study therefore aimed to investigate trauma levels in IAPT patients. Method: A total of 54 participants were recruited at the beginning of therapy within an IAPT service. Participants completed outcome measures for anxiety, depression and trauma. Results: Forty (76.9%)  participants reported previous trauma. Of  these, 15  (28.3%)  met  tentative diagnostic criteria for PTSD, with only 3 (14.2%) already having a diagnosis of PTSD. Significant positive correlations were found between trauma and anxiety and  depression. Conclusions: The findings suggest comorbidity between trauma/PTSD and anxiety and depression in IAPT services. The findings also show that PTSD is not always detected in patients referred for other reasons. It is proposed that careful screening for PTSD and an increased focus on trauma in supervision may increase recovery rates and reduce relapse